Pengaruh Berbagai Dosis Pupuk Kalium dan Silika terhadap Produksi Cabai Rawit (Capsicum frutescens L.): The Effect of Various Doses of Potassium and Silica Fertilizer on Cayenne Pepper (Capsicum frutescens L.) Production - Farida Jufri, Afifah; Nurrachman, Nurrachman; Pranggawan Azhari, Anjar; Jihadi, Amrul; Martia Dewi, Suprayanti (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
The instability of cayenne pepper production is caused by the high rate of flower and fruit loss. This research aims to determine the effect of a combination of potassium and silica fertilizer on the production of cayenne pepper plants. The research was conducted in Rembige Village, Selaparang District, Mataram City for 6 months from April-October 2024. The materials used were Ori 212 variety, 20% liquid silica (SiO4), and KCl (60%K2O). The design used is Factorial RAK with two factors. The first factor is the dose of KCl fertilizer with 3 treatment levels, a dose of 150 kg ha-1 (K1), 300 kg ha-1 (K2) and 450 kg ha-1 (K3). The second factor is the concentration of silica fertilizer with 2 treatment levels, without silica (S0) and 2ml L-1 silica (S1). Each experimental unit was carried out 3 times and each repetition carried out observations on 5 plants. Observations and data collection include the number of productive branches, number of flowers, fruit set percentage, number of fruit per plant, and fruit weight per plant. The research results were analyzed using analysis of variance, and a 5% BNJ follow-up test. The results showed that there was an interaction between potassium and silica fertilizer treatments on fruit set parameters. Plants with a potassium dose of 150 kg ha-1 without silica gave the lowest fruit set yield, namely 60.74%. Potassium and silica had significantly different effects on all observation parameters, where a dose of 300 kg ha-1 of potassium and 2 ml L-1 of silica gave the best results.